The stabilizing effect of scale breeding on swine production volatility-empirical evidence from China - Jiang, Hui; Wang, Mingli; Yan, Zhaohui; Sun, Yumeng (Frontiers in Sustainable Food Systems, 2024)
Introduction In the pursuit of agricultural sustainability and food security, the stability of livestock production under large-scale operations plays a pivotal role. Methods Based on panel data from 26 provinces in China spanning the years 2007 to 2020, this study employs a two-way panel fixed effects model to examine the stabilizing effect of scale breeding on swine production volatility in China. Additionally, it utilizes the moderating effect model to examine the moderating effect of epidemic risk and policy intervention, and uses the threshold effect model to test the threshold effect of marketization level. Results Empirical evidence indicates that moderate-scale breeding exerts a stabilizing effect on swine production volatility, with this effect displaying regional disparities. From the external situation, the higher the risk of epidemic disease, the stronger the stable effect of scale breeding on the fluctuation of swine production, while the enhancement of policy intervention cannot promote the stability of scale breeding on swine production volatility. There is a single threshold effect on the impact of scale breeding on swine production volatility. When the degree of marketization reaches a certain level, the stabilizing effect of scale breeding on swine production volatility is enhanced. Discussion Therefore, it is recommended to promote the moderately scaled swine breeding, enhance epidemic monitoring and information disclosure systems, reduce excessive policy intervention, and fully leverage the self-regulating role of the market.